2004
DOI: 10.1074/jbc.m401203200
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[c]phenanthrene Adducts and Nogalamycin Inhibit DNA Transesterification by Vaccinia Topoisomerase

Abstract: Vaccinia DNA topoisomerase forms a covalent DNA-(3-phosphotyrosyl)-enzyme intermediate at a specific target site 5-C ؉5 C ؉4 C ؉3 T ؉2 T ؉1 p2N ؊1 in duplex DNA. Here we study the effects of position-specific DNA intercalators on the rate and extent of single-turnover DNA transesterification. Chiral C-1 R and S trans-opened 3,4-diol 1,2-epoxide adducts of benzo[c]phenanthrene (BcPh) were introduced at single N 2 -deoxyguanosine and N 6 -deoxyadenosine positions within the 3-sequence of the nonscissile DNA stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Role of the Ϫ1 Base in DNA Cleavage-Vaccinia topoisomerase displays no preference for a particular base pair immediately 3Ј of the scissile phosphodiester (1,18). Here we found that an abasic lesion at Ϫ1 on the scissile strand slowed k cl by a factor of 350, whereas a Ϫ1 abasic lesion on the nonscissile strand had no effect at all.…”
Section: Position-specific Abasic Interference With Dna Religation-mentioning
confidence: 99%
See 2 more Smart Citations
“…Role of the Ϫ1 Base in DNA Cleavage-Vaccinia topoisomerase displays no preference for a particular base pair immediately 3Ј of the scissile phosphodiester (1,18). Here we found that an abasic lesion at Ϫ1 on the scissile strand slowed k cl by a factor of 350, whereas a Ϫ1 abasic lesion on the nonscissile strand had no effect at all.…”
Section: Position-specific Abasic Interference With Dna Religation-mentioning
confidence: 99%
“…Recent studies have focused on delineating the features of the DNA interface that affect the kinetics of transesterification. For example, positionspecific covalent polycyclic aromatic hydrocarbon diol epoxide-DNA adducts have been exploited to probe the minor groove interface (16) and the effects of intercalation at all of the dinucleotides steps spanning the target site (17,18). The aromatic hydrocarbon adduct studies delineated the margins of the functional DNA interface at atomic resolution but did not reveal the nature of the DNA contacts within the essential zone of DNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Position-specific base modifications have been used to systematically address the features of the individual target site bases that affect the kinetics of DNA transesterification (13)(14)(15)(16)(17). The sensitivity of this method depends on the degree to which the particular modification alters the size, shape, stacking, and hydrogen-bonding potential of the base or base pair.…”
mentioning
confidence: 99%
“…For instance, site-specific modification with benzo-[c]-phenanthrene at N2 and N6 of G can reduce the cleavage rate by a factor of 1000 (6), and site-specific modification of the exocylic amino groups of the +1 and +2 adenines with benzo-[a]-pyrene decreased the rate of cleavage by approximately 10 3 -fold (15). The rate effects on strand cleavage arising from the more subtle major groove modifications of 8-oxoguanine, 8-oxoadenine and 2-aminopurine have also been explored, where deleterious effects as large as 35-fold at the +3G were observed (15).…”
mentioning
confidence: 99%